Lane detection and tracking algorithm implementation for an Ackermann-steering mobile robot - Pérez, Joaquín; Aillaud, León VIII; Astorga, Rafael; Orozco Rosas, Ulises; Picos, Kenia (My University, 2023)
This paper presents the implementation of a lane detection and tracking algorithm for the autonomous navigation of an Ackermann-steering mobile robot. The proposed implementation employs an RGB camera mounted on the robot, the image information is processed through the lane detection and tracking algorithm to define the robot’s present and future position within the lane. This information is used to determine the orientation of the wheels required to steer the robot within the lane. The implementation employs a Raspberry Pi as the primary logic controller to process the image received from the RGB camera. The Ackermann-steering mobile robot performs steering and navigation with a proportional-integral-derivative controller that manages the orientation of the steering. Experimental results are presented to validate the implementation considering a physical implementation of the Ackermann-steering mobile robot.
Keywords: Algoritmo de detección; Robot móvil de dirección; Campus Tijuana